Mitigating Clonal Variation in Recombinant Mammalian Cell Lines - Lee, Jae Seong; Kildegaard, Helene Faustrup; Lewis, Nathan E.; Lee, Gyun Min (Trends in Biotechnology, 2019)
Mammalian expression platforms are primary production systems for therapeutic proteins that require complex post-translational modifications. Current processes used for developing recombinant mammalian cell lines generate clonal cell lines with high phenotypic heterogeneity, which has puzzled researchers that use mammalian cell culture systems for a long time. Advances in mammalian genome-editing technologies and systems biotechnology have shed light on clonal variation and enabled rational cell engineering in a targeted manner. We propose a new approach for a next-generation cell line development platform that can minimize clonal variation. Combined with the knowledge-based selection of ideal integration sites and engineering targets, targeted integration-based cell line development will allow tailored control of recombinant gene expression with predicted phenotypes.
Keywords: Cell lines; Clonal variations; Development platform; Mammalian cell culture; Mammalian cell lines; Post-translational modifications; Recombinant gene expressions; Transgene; Animals; Cell Engineering; Cell Line; Gene Editing; Genetic Engineering; Mammals; Recombinant Proteins; cell line development; clonal variation; rational cell engineering; transgene integration